Relationship Between Nutrition Knowledge, Diet, Glycaemic Index with Blood Sugar Levels of Diabetes Mellitus Patients - Salsabilla, Putri; Maigoda, Tonny Cortis; Rizal, Ahmad; Wahyudi, Anang; Witradharma, Tetes Wahyu; Hari Hariadi (Research and Social Study Institute, 2024)
Diabetes Mellitus (DM) is one type of degenerative disease that has increased every year in countries around the world, including Indonesia. The purpose of this study was to determine the relationship between nutritional knowledge, diet and glycemic index status with blood sugar levels during type II DM patients at Pasar Ikan City Health Center. Bengkulu in 2024. Methods Analytic observation research with cross sectional design. 55 people with type II DM as a sample taken with simple random sampling technique. Nutritional knowledge was measured using a questionnaire, while diet and glycemic index status were measured using the Semi Quantitative Food Frequency Questionnaire (SQ-FFQ) form. Intermittent blood sugar levels were measured using the Nesco Multicheck tool. Univariate and bivariate data analysis was processed using SPSS software with chi square test with a significance value of α=0.05. Results: There were 80% of respondents with poor knowledge, 89.5% with poor diet, and 82.1% with high glycemic index status. Conclusion: There is a relationship between nutritional knowledge, diet, glycemic index status, and the biggest influence is diet.